Air‐Water Interfaces: Interfaces Determine the Fate of Seeded α‐Synuclein Aggregation (Adv. Mater. Interfaces 11/2020). Issue 11 (10th June 2020) - Campioni, Silvia; Bagnani, Massimo; Pinotsi, Dorothea; Lecinski, Sarah; Rodighiero, Simona; Adamcik, Jozef; Mezzenga, Raffaele
Abstract : The cover shows that when mixtures of alpha‐Synuclein fibrils (in green) and monomeric alpha‐Synuclein (in red) are incubated in presence of the air, short and thick dual‐color fibrils form at the air‐water interface. In absence of air‐water, fewer, longer and thinner fibrils form in bulk. More details can be found in article number 2000446 by Silvia Campioni, Raffaele Mezzenga, and co‐workers.